Comparative Effects of Atorvastatin and its Liposomal Preparation in Impeding the Migratory Potential of Colorectal Cancer Cell Line HT-29 (Medical Forum Monthly, 2023)
Objective: The objective of my study is to evaluate the effects of Atorvastatin and its liposomal conjugation (lipo-ATO) as an anti-migratory potential in colorectal cancer HT-29 cell line.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at the Clifton campus of Ziauddin University, Karachi from 15 October, 2022 to July, 2023.Materials and Methods: After revival, cells were plated in 6 well plates with complete media, a vertical scratch was made with 10µl pipette and different drugs were added in each group. Images of the cells were observed at interval of 24, 48, 72, and 96 hrs. Under an inverted microscope, to determine the difference in wound healing.Results: The result of our study showed that liposomal atorvastatin significantly delayed wound healing as compared to free atorvastatin and 5-FU P-value(>0.001).However, free atorvastatin produced cytotoxicity at 72hrs.Conclusion: Liposomal conjugated atorvastatin showed pronounced anti-migratory effects in HT-29 cell line by delaying wound healing. Comprehensive studies are warranted to confirm the findings and to appraise underlying molecular mechanisms.